English: English - Kicki Herdayanti; Robby Satria (Universitas Putera Batam, 2021)
This research was useful for knowing the personality of the main character in the film. The researchers used the film Lady Bird as the object of research because this film was very interesting and told the story of a teenager who had very strong ambitions. This film was written by Greta Gerwig in 2017. The researcher used the psychoanalytic theory by Sigmund Freud. The study aimed to analyze the psychological conflict between ego, id and super ego trough the attitude and utterances of the main character. The method was qualitative descriptive. In result, researchers found 6 aspects of the id that are directly related to the main character, 2 aspects of the ego and 2 aspects of the superego. Therefore, the researcher concludes that in the main character in this film, she was more controlled by his id, where she was a form of personality that a person carried when she was born. The Id on Ladybird showed how she fulfilled a wish she deserved and felt that she enjoyed it more without realizing it.